Pengaplikasian Tata Kelola Keuangan Islam Dalam Perbankan Syariah di Indonesia - Elinda Vira Yusifa; Fifi Hamidah Permatasari; Agus Eko Sujianto (Pusat Riset dan Inovasi Nasional, 2023)
This research suggests a connection between sharia banking and sharia governance, particularly in Indonesia. The qualitative data for the study were gathered using the library approach. In this study, secondary data from books and articles on the subject that were gathered from reputable research publications were utilised. The necessity for sharia banking services as well as the expanding diversity of products are what are driving the growth of the sharia banking business. The findings of the literature research indicate that it is crucial for the Islamic banking sector to understand how popular it is becoming. All organisations under oppression need Islamic governance because it promotes and upholds Islamic banking and finance. The findings of this study suggest that Bank Indonesia laws control the application of Islamic sharia in Indonesia. Indonesian sharia banking must comply to sharia principles and is governed by a number of laws and regulations pertaining to the conduct of transactions. However, Indonesian Islamic banks have not yet been able to incorporate Islamic governance into their day-to-day activities.